Heat-resistant polyurethane structural adhesive and preparation method thereof

By using multi-arm polyethylene glycol maleimide and mercaptoalkyl alcohol, the imidyl polyol obtained by reacting multi-arm polyethylene glycol maleimide and mercaptoalkyl alcohol, combined with a trifunctional polyol crosslinking agent, the heat resistance of polyurethane structural glue is improved, and the solution is solved The problem of degraded bonding performance of power batteries at high temperatures ensures battery safety.

CN119307217APending Publication Date: 2025-01-14COLLTECH DONGGUAN BONDING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411435340.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The power battery generates heat during charging and discharging, especially in high-speed charging and high-temperature environments. The existing polyurethane structural glue lacks heat resistance, which may lead to safety accidents such as short circuits, fires or explosions inside the battery.

Method used

Imide-based polyol prepared by reacting polyamide polyethylene glycol maleimide with mercaptoalkyl alcohol is used as the raw material for synthesis of polyurethane, combining trifunctional polyol crosslinking agent and polymer diol to adjust cross-section The linkage degree and crosslinking point structure improve the heat resistance of polyurethane structural glue.

Benefits of technology

It significantly improves the heat resistance of polyurethane structural adhesives, ensures that the adhesive performance is maintained at high temperatures, and avoids battery safety accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005084783850000051
    Figure BDA0005084783850000051
  • Figure BDA0005084783850000061
    Figure BDA0005084783850000061
Patent Text Reader

Abstract

The invention provides a heat-resistant polyurethane structural adhesive and a preparation method thereof, the heat-resistant polyurethane structural adhesive comprises a component A and a component B in a mass ratio of (1-1.5): 1, the component A comprises the following raw materials in parts by weight: 30-40 parts of imide polyol, 10-20 parts of polymer diol, 0.5-1 part of a trifunctional polyol cross-linking agent, 25-50 parts of a filler, 1-3 parts of a coupling agent, 1-3 parts of a thixotropic agent and 0.3-0.5 part of a tin catalyst; the imidogen polyol is prepared by reacting multi-arm polyethylene glycol maleimide with sulfydryl alkyl alcohol, wherein the molar ratio of a maleimide group in the multi-arm polyethylene glycol maleimide to a sulfydryl group in the sulfydryl alkyl alcohol is 1: (2.4-3); the component B is prepared from the following raw materials in parts by weight: 40 to 60 parts of diisocyanate, 25 to 50 parts of filler and 1 to 3 parts of coupling agent. The cross-linking degree of the polyurethane structural adhesive and the structural form and size of a cross-linking point are adjusted, so that the heat resistance of the polyurethane structural adhesive is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane structural adhesives, and particularly relates to a heat-resistant polyurethane structural adhesive and a preparation method thereof. Background Art

[0002] At present, the requirements for automobile fuel economy and emission performance are becoming increasingly stringent, which has led to the rapid development of new energy vehicles including pure electric vehicles and plug-in hybrid vehicles. As one of the most critical components of new energy vehicles, power batteries provide a power source for them and directly affect the performance of new energy vehicles such as cruising range, safety, service life, charging time and temperature adaptability.

[0003] As a new type of connection method, bonding technology can achieve the connection of dissimilar materials without damaging the connection materials. In addition, the adhesive structure has the advantages of reducing the weight of the vehicle body structure, large load-bearing area, and uniform stress distribution on the adhesive surface. Two-component polyurethane structural adhesive has the characteristics of light weight, high toughness, good insulation, vibration resistance and vibration reduction, and is widely used. At present, it is being adopted in the assembly and installation stages of power batteries in more and more new energy vehicles. It can not only replace traditional mechanical connection methods such as rivets, bolts and even welding to achieve structural bonding and sealing, but also reduce the weight of the vehicle to achieve energy conservation and emission reduction.

[0004] Patent CN111303820B discloses a two-component polyurethane structural adhesive for bonding power batteries and a preparation method thereof, wherein the polyurethane structural adhesive comprises component A and component B; component A comprises 40 to 65 parts of polymethylene polyphenyl isocyanate, 30 to 50 parts of aluminum hydroxide, 2 to 5 parts of hydrophobic fumed silica, and 0 to 5 parts of a plasticizer; component B comprises 40 to 65 parts of a bio-based polyol, 1 to 4 parts of fumed silica, 25 to 50 parts of a flame retardant, 1 to 5 parts of an adhesion promoter, and 0.01 to 0.5 parts of a catalyst; the bio-based polyol is selected from one or more of a rapeseed oil-modified polyol, a castor oil-modified polyol, a soybean oil-modified polyol, and a palm oil-modified polyol; the adhesion promoter is prepared by reacting aminophenylsilane with a silane modifier. Patent CN115260972B discloses a bio-based two-component polyurethane structural adhesive, which consists of a main agent component A and a curing agent component B. Component A includes 3-37 parts of polyol, 0.1-2 parts of auxiliary agent, and 12-46 parts of filler; component B includes 3-37 parts of bio-based polyurethane prepolymer, 0.2-2 parts of auxiliary agent, and 12-46 parts of filler.

[0005] During the charging and discharging process, power batteries generate heat, especially during high-speed charging and high-temperature environments. The internal temperature of the battery rises, and polyurethane structural adhesives have poor heat resistance and will soften or even melt at high temperatures, with a significant drop in bonding performance, which may lead to safety accidents such as short circuits, fires or explosions inside the battery. Therefore, it is necessary to develop a heat-resistant polyurethane structural adhesive and its preparation method. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a heat-resistant polyurethane structural adhesive and a preparation method thereof. The imide polyol prepared by the reaction of multi-arm polyethylene glycol maleimide and mercaptoalkyl alcohol in component A is used as one of the polyurethane synthesis raw materials - polyol polymer. The strong polarity of the imide group is used to improve the intermolecular force of the polyurethane structural adhesive, thereby improving the heat resistance. The imide group is a planar rigid structure that can stabilize the molecular structure at high temperature. The imide group is used in combination with a trifunctional polyol crosslinking agent and a polymer diol to adjust the crosslinking degree of the polyurethane structural adhesive, as well as the structural morphology and size of the crosslinking points, thereby improving the heat resistance of the polyurethane structural adhesive.

[0007] In order to achieve the above object, the present invention adopts the following specific technical scheme:

[0008] A heat-resistant polyurethane structural adhesive comprises components A and B, wherein the mass ratio of components A to B is 1-1.5:1.

[0009] The component A comprises the following raw materials in parts by weight: 30-40 parts of imido polyol, 10-20 parts of polymer diol, 0.5-1 parts of trifunctional polyol crosslinking agent, 25-50 parts of filler, 1-3 parts of coupling agent, 1-3 parts of thixotropic agent, and 0.3-0.5 parts of tin catalyst; the imido polyol is prepared by reacting multi-arm polyethylene glycol maleimide with mercaptoalkyl alcohol, wherein the molar ratio of maleimide group in multi-arm polyethylene glycol maleimide to mercapto group in mercaptoalkyl alcohol is 1:2.4-3.

[0010] The B component comprises the following raw materials in parts by weight: 40-60 parts of diisocyanate, 25-50 parts of filler, and 1-3 parts of coupling agent. The multi-arm polyethylene glycol maleimide has a number average molecular weight of 2000-5000, preferably 2000-3400, and is specifically selected from one or a combination of six-arm polyethylene glycol maleimide and eight-arm polyethylene glycol maleimide.

[0011] The mercaptoalkyl alcohol is a straight-chain alkyl alcohol having 6 to 10 carbon atoms, selected from one or a combination of two or more of 6-mercapto-1-hexanol, 8-mercapto-1-octanol, 9-mercapto-1-nonanol, and 10-mercapto-1-decanol.

[0012] The imide polyol is prepared by a method comprising the following steps:

[0013] The multi-arm polyethylene glycol maleimide, mercaptoalkyl alcohol and catalyst are added to an organic solvent, and reacted under temperature-controlled stirring conditions. After the reaction is completed, carbon tetrachloride is added to the reaction system until no precipitation is generated, and the system is filtered, washed and vacuum-dried to obtain the imide polyol.

[0014] The temperature control is to control the temperature at 20-40°C, and the stirring speed is 100-300r / min. The reaction time is 3-5h. The inhibitor is selected from one or a combination of two or more of phenol, hydroquinone, and p-hydroxyanisole. The organic solvent is selected from one or a combination of two or more of DMF, DMSO, dichloromethane, chloroform, dichloroethane, benzene, and carbon tetrachloride; preferably, a mixed solvent of DMF and dichloroethane in a volume ratio of 1:10-12. The catalyst is selected from one or a combination of two or more of triethylamine, triethylenediamine, dimethylcyclohexylamine, and N-methyldicyclohexylamine; the amount of the catalyst is 1-1.5wt% of the mass and weight of multi-arm polyethylene glycol maleimide and mercaptoalkyl alcohol. The washing is washed with carbon tetrachloride 1-3 times, and the vacuum drying temperature is 80-100°C. The diisocyanate is selected from one or a combination of two of toluene diisocyanate and diphenylmethane diisocyanate.

[0015] The polymer diol is a polyester diol or a polyether diol with a number average molecular weight of 1000-2000.

[0016] The trifunctional polyol crosslinking agent is selected from glycerol, trimethylolpropane or a combination of the two.

[0017] The filler has a median particle size of 1-20 μm and is selected from one or a combination of two or more of alumina, magnesium oxide, aluminum nitride, boron nitride, aluminum hydroxide, magnesium hydroxide, silicon carbide, calcium carbonate, silicon micropowder, talc, kaolin, and attapulgite.

[0018] The coupling agent is an epoxysilane coupling agent, selected from 3-(2,3-epoxypropyl)trimethoxysilane, 3-(2,3-epoxypropyl)triethoxysilane, 3-(2,3-epoxypropyl)methyldimethoxysilane, 3-(2,3-epoxypropyl)methyldiethoxysilane, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexane)ethyltriethoxysilane, or a combination of two or more thereof.

[0019] The thixotropic agent has a specific surface area of ​​100-500m 2 / g of fumed silica.

[0020] The tin catalyst is not particularly limited, and includes but is not limited to one or a combination of two or more of stannous octoate, stannous oleate, and dibutyltin dilaurate.

[0021] The present invention also provides a method for preparing the heat-resistant polyurethane structural adhesive, comprising the following steps:

[0022] 1) adding an imide polyol, a polymer diol, and a trifunctional polyol crosslinking agent into a mixing kettle, heating and mixing them uniformly under vacuum conditions, cooling and adding a filler, a thixotropic agent, a tin catalyst, and a coupling agent, and mixing them uniformly to obtain component A;

[0023] 2) mixing diisocyanate, filler and coupling agent uniformly to obtain component B;

[0024] 3) Evenly mix components A and B to obtain heat-resistant polyurethane structural adhesive.

[0025] In step 1), the temperature is raised to 100-120°C, and the temperature is lowered to 60-70°C.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The imide polyol prepared by the reaction of multi-arm polyethylene glycol maleimide and mercaptoalkyl alcohol in component A of the present invention is used as one of the polyurethane synthesis raw materials - polyol polymer, and the strong polarity of the imide group is used to improve the intermolecular force of the polyurethane structural adhesive, thereby improving the heat resistance; the imide group is a planar rigid structure that can stabilize the molecular structure at high temperature, and is used in combination with a trifunctional trifunctional polyol crosslinking agent and a polymer diol to adjust the crosslinking degree of the polyurethane structural adhesive, as well as the structural morphology and size of the crosslinking points, thereby improving the heat resistance of the polyurethane structural adhesive. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.

[0029] Eight-arm polyethylene glycol maleimide was purchased from Shanghai Zhenzhun Biotechnology Co., Ltd. with a number average molecular weight of 1000 and a product number of ZP-73204.

[0030] Eight-arm polyethylene glycol maleimide was purchased from Shanghai Zhenzhun Biotechnology Co., Ltd. with a number average molecular weight of 2000 and a product number of ZP-73205.

[0031] Eight-arm polyethylene glycol maleimide was purchased from Shanghai Zhenzhun Biotechnology Co., Ltd. with a number average molecular weight of 3400 and a product number of ZP-73206.

[0032] Eight-arm polyethylene glycol maleimide was purchased from Shanghai Zhenzhun Biotechnology Co., Ltd. with a number average molecular weight of 5000 and a product number of ZP-73207.

[0033] Six-arm polyethylene glycol maleimide was purchased from Shaanxi Xinyan Bomei Biotechnology Co., Ltd. with a number average molecular weight of 2000.

[0034] The number average molecular weights of polypropylene glycol were 1000 and 2000, respectively, and they were purchased from Shanghai Beko Chemical Co., Ltd.

[0035] Aluminum hydroxide was purchased from Guangdong Jinge New Materials Co., Ltd. with a brand name of FA-70 and a D50 of 6.5 μm.

[0036] Preparation of heat-resistant polyurethane structural adhesive

[0037] Example 1

[0038] 1) 0.0125 mol of eight-arm polyethylene glycol maleimide ZP-73205, 0.3 mol of 10-mercapto-1-decanol (the molar ratio of maleimide group:mercapto group is 1:3), and 0.83 g of triethylamine are added to a mixed solvent of 100 mL of DMF and ethylene dichloride in a volume ratio of 1:10, and the mixture is stirred at a speed of 120 r / min and the temperature is controlled at 25° C. for 3 h. After the reaction is completed, carbon tetrachloride is added to the reaction system until no precipitation is generated, filtered, washed with carbon tetrachloride 3 times, and vacuum dried at 80° C. to constant weight to obtain imide polyol.

[0039] 2) 400 g of the imide polyol obtained by the method in step 1), 200 g of polypropylene glycol with a number average molecular weight of 2000, and 5 g of propylene glycol were added to a mixing kettle, the temperature was raised to 100° C., and the mixture was mixed evenly at -0.1 MPa, the temperature was lowered to 60° C., 500 g of FA-70, 30 g of fumed silica Evonik R-202, 5 g of dibutyltin dilaurate, and 3 g of 3-(2,3-epoxypropyl)trimethoxysilane were added, and the mixture was mixed evenly to obtain component A;

[0040] 3) 600 g of diphenylmethane diisocyanate, 500 g of FA-70, and 30 g of 3-(2,3-epoxypropyl)trimethoxysilane were uniformly mixed to obtain component B;

[0041] 4) Take components A and B in a mass ratio of 1:1 and mix them evenly to obtain a heat-resistant polyurethane structural adhesive.

[0042] Example 2

[0043] The rest is the same as Example 1, except that in step 1), 0.017 mol of six-arm polyethylene glycol maleimide is used to replace eight-arm polyethylene glycol maleimide ZP-73202.

[0044] Example 3

[0045] The rest is the same as Example 1, except that the amount of 10-mercapto-1-decanol used in step 1) is 0.24 mol.

[0046] Example 4

[0047] The rest is the same as Example 1, except that in step 1), an equimolar amount of ZP-73206 is used to replace ZP-73205.

[0048] Example 5

[0049] The rest is the same as Example 1, except that in step 1), an equimolar amount of ZP-73207 is used to replace ZP-73205.

[0050] Example 6

[0051] The rest is the same as Example 1, except that in step 1), an equimolar amount of ZP-73204 is used to replace ZP-73205.

[0052] Example 7

[0053] The rest is the same as Example 1, except that the amount of imide polyol used in step 2) is 300 g.

[0054] Example 8

[0055] The rest is the same as Example 1, except that in step 2), an equal mass of polypropylene glycol with a number average molecular weight of 1000 is used to replace the polypropylene glycol with a number average molecular weight of 2000.

[0056] Example 9

[0057] The rest is the same as Example 1, except that:

[0058] Step 2) Take 400g of the imide polyol obtained by the method in step 1), 100g of polypropylene glycol with a number average molecular weight of 2000, and 10g of propylene glycol, add them into a mixing kettle, heat to 100°C, mix evenly at -0.1MPa, cool to 60°C, add 500g FA-70, 30g of fumed silica Evonik R-202, 5g of dibutyltin dilaurate, and 3g of 3-(2,3-epoxypropyl)trimethoxysilane, mix evenly, and obtain component A;

[0059] Step 3) 400 g of diphenylmethane diisocyanate, 500 g of FA-70, and 30 g of 3-(2,3-epoxypropyl)trimethoxysilane were uniformly mixed to obtain component B.

[0060] Comparative Example 1

[0061] The rest is the same as Example 1, except that pentaerythritol is used instead of glycerol, and the number of hydroxyl groups of pentaerythritol and glycerol is the same.

[0062] Comparative Example 2

[0063] The rest is the same as Example 1, except that the imide polyol is replaced by an equal mass of polypropylene glycol having a number average molecular weight of 2000.

[0064] The heat-resistant polyurethane structural adhesives prepared in the above examples and comparative examples were subjected to the following performance tests:

[0065] 1. Adhesive performance: Refer to GB / T 7124-2008 for the determination of tensile shear strength of adhesives. The PET blue film without primer and surface treatment and 3003 aluminum material are bonded to each other to prepare shear test pieces. The thickness of the adhesive layer on both sides of the PET blue film is 0.2mm, and the bonding area is 25mm*12.5mm. The shear test pieces are cured for 7 days at a temperature of 23±2℃ and a relative humidity of 50±5%. The tensile shear strength at room temperature and 65℃ is tested, and the tensile speed is 100mm / min.

[0066] 2. Modulus: DMA8000 dynamic thermomechanical analyzer was used, the tensile method was adopted, the frequency was 500 Hz, the heating rate was 20-200°C, and the modulus data at 25°C were obtained from the analysis curve.

[0067] Table 1 Performance test results

[0068]

[0069]

[0070] It can be seen from the examples and comparative example 1 that the amount and molecular weight of the imide polyol, polymer diol, and trifunctional chain extender have a significant effect on the bonding properties of the polyurethane structural adhesive at high temperatures.

[0071] It can be seen from Example 1 and Example 8 that by reducing the molecular weight of polypropylene glycol, the polyurethane structural adhesive exhibits a certain brittleness and the shear strength shows a downward trend.

[0072] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A heat-resistant polyurethane structural adhesive, characterized in that: It includes components A and B, and the mass ratio of components A and B is 1-1.5:

1. The component A comprises the following raw materials in parts by weight: 30-40 parts of imido polyol, 10-20 parts of polymer diol, 0.5-1 parts of trifunctional polyol crosslinking agent, 25-50 parts of filler, 1-3 parts of coupling agent, 1-3 parts of thixotropic agent, and 0.3-0.5 parts of tin catalyst; the imido polyol is prepared by reacting multi-arm polyethylene glycol maleimide with mercaptoalkyl alcohol, wherein the molar ratio of maleimide group in multi-arm polyethylene glycol maleimide to mercapto group in mercaptoalkyl alcohol is 1:2.4-3; The component B comprises the following raw materials in parts by weight: 40-60 parts of diisocyanate, 25-50 parts of filler, and 1-3 parts of coupling agent.

2. The heat-resistant polyurethane structural adhesive according to claim 1, characterized in that: The multi-arm polyethylene glycol maleimide has a number average molecular weight of 2000-5000, preferably 2000-3400, and is selected from one or a combination of six-arm polyethylene glycol maleimide and eight-arm polyethylene glycol maleimide.

3. The heat-resistant polyurethane structural adhesive according to claim 1, characterized in that: The mercaptoalkyl alcohol is a straight-chain alkyl alcohol having 6 to 10 carbon atoms, selected from one or a combination of two or more of 6-mercapto-1-hexanol, 8-mercapto-1-octanol, 9-mercapto-1-nonanol, and 10-mercapto-1-decanol.

4. The heat-resistant polyurethane structural adhesive according to claim 1, characterized in that: The imide polyol is prepared by a method comprising the following steps: The multi-arm polyethylene glycol maleimide, mercaptoalkyl alcohol and catalyst are added to an organic solvent, and reacted under temperature-controlled stirring conditions. After the reaction is completed, carbon tetrachloride is added to the reaction system until no precipitation is generated, and the system is filtered, washed and vacuum-dried to obtain the imide polyol.

5. The heat-resistant polyurethane structural adhesive according to claim 4, characterized in that: The temperature control is to control the temperature at 20-40°C, the stirring speed is 100-300r / min, and the reaction time is 3-5h.

6. The heat-resistant polyurethane structural adhesive according to claim 4, characterized in that: The inhibitor is selected from one or a combination of two or more of phenol, hydroquinone, and p-hydroxyanisole; the organic solvent is selected from one or a combination of two or more of DMF, DMSO, dichloromethane, chloroform, dichloroethane, benzene, and carbon tetrachloride; preferably, it is a mixed solvent of DMF and dichloroethane in a volume ratio of 1:10-12.

7. The heat-resistant polyurethane structural adhesive according to claim 4, characterized in that: The catalyst is selected from one or a combination of two or more of triethylamine, triethylenediamine, dimethylcyclohexylamine, and N-methyldicyclohexylamine; the amount of the catalyst is 1-1.5wt% of the sum of the mass of multi-arm polyethylene glycol maleimide and mercaptoalkyl alcohol.

8. The heat-resistant polyurethane structural adhesive according to claim 1, characterized in that: The diisocyanate is selected from toluene diisocyanate, diphenylmethane diisocyanate or a combination of the two; the polymer diol is a polyester diol or a polyether diol with a number average molecular weight of 1000-2000.

9. The heat-resistant polyurethane structural adhesive according to claim 1, characterized in that: The trifunctional polyol crosslinking agent is selected from glycerol, trimethylolpropane or a combination of the two.

10. The method for preparing the heat-resistant polyurethane structural adhesive according to any one of claims 1 to 9, comprising the following steps: 1) adding an imide polyol, a polymer diol, and a trifunctional polyol crosslinking agent into a mixing kettle, heating and mixing them uniformly under vacuum conditions, cooling and adding a filler, a thixotropic agent, a tin catalyst, and a coupling agent, and mixing them uniformly to obtain component A; 2) mixing diisocyanate, filler and coupling agent uniformly to obtain component B; 3) Evenly mix components A and B to obtain heat-resistant polyurethane structural adhesive.

Citation Information

Patent Citations

  • A two-component polyurethane structural adhesive for bonding power batteries and its preparation method

    CN111303820B

  • Bio-based two-component polyurethane structural adhesive

    CN115260972B